PATTERNS OF SPATIAL AND TEMPORAL DISTRIBUTION OF AGROCLIMATIC RESOURCES: (Ararat Valley and foothill zone) (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The paper analyzes and evaluates the regularities of the spatial distribution of agroclimatic resources of the Ararat Valley and the foothill zone, the long-term course and tendency of change, and suggests ways of regulating the consequences of their change.
Keywords: agroclimatic resource; photosynthetic active radiation; heat supply; moisture supply; spatiotemporal distribution; Ararat Valley and foothills